Vision & strategy : strategic thinking for creative and social entrepreneurs - Rothauer, Doris, (Birkhauser, 2018)
Creative and social entrepreneurs are at the forefront of building a new economy and shaping our future by being highly visionary and following their path persistently. Visions are the driving force for social innovation. But, without a strategy on how to achieve our vision, the vision stays a vision and consequently will have zero impact. Therefore, visions need strategies. Vice versa, strategies need to be based on visions in order to be powerful. Business development without following a visionary strategy leaves the future to chance. In times where complexity and the pace of change is constantly rising this does not work anymore. This book helps to understand the connection between strategy and vision, strategy and creativity. It follows an approach to strategy as a meaningful, playful, experimental and therefore creative way to design a sustainable and impactful future. Included are a selection of effective tools and methods on how to develop a strategic thinking.